Detection of Metastatic Disease in Cardiophrenic Lymph Nodes: FDG PET/CT Versus Contrast-Enhanced CT and Implications for Staging and Treatment of Disease - Farmakis, Shannon; Vejdani, Kaveh; Muzaffar, Razi; Parkar, Nadeem; Osman, Medhat M. (Frontiers in Oncology, 2013)
Objective: To determine whether FDG PET/CT was more sensitive than CT in detecting metastatic disease in the cardiophrenic space and whether the presence of disease in this location would change the staging and clinical management. Methods: 1200 PET/CT scans were retrospectively reviewed over 20 months for the presence of FDG-avid cardiophrenic lymph nodes. The SUVmax was used to quantify the metabolic activity in each of the lymph nodes. The radiographic data was used for correlation. A retrospective review of diagnostic CT reports performed within a one month period of time of the PET/CT in the same subset of patients determined whether cardiophrenic lymph nodes were mentioned. Results: 9 (0.8%) of the 1200 studies were found to have FDG-avid cardiophrenic lymph nodes (4 males and 5 females with a mean age of 55 years; range 7-69, median 59). The mean SUVmax was 2.4 (range 1.2-7.9; median 1.9). Only 3 of the patients were found to have suspicious lymph nodes on CT. The presence of cardiophrenic lymph nodes had the potential to change the staging and/or management in 3 of the patients. Conclusion: PET/CT is more accurate in the detection of pathologic cardiophrenic lymph nodes than CT, especially when they are subcentimeter in size. When present, staging and/or management was potentially affected in 33%. Therefore, these nodes should be included in the TNM staging classification.